General overview of traditional healer practices in relation to mental health in Sudan,Sorcetti - Sorketti, E.A. (http://www.arabpsynet.com/, 2008)
Traditional beliefs and religion play an important role in the socio-cultural and political life of the people in the countries of the Eastern Mediterranean Region. The family and community hold a central position in the life of the individual, and they make a tremendous contribution to the therapeutic process. Native faith healers are found in all parts of the Region, where they are held in high regard and are considered to be spiritual or moral guides. They are consulted for a range of ailments including physical illness, emotional problems, congenital defects or disappointments in love, family or business. The WHO studies of pathways to care have shown native faith healers to be an important source of care for people who ultimately attend psychiatric services. In Sudan a symbiotic working relationship has been developed with faith healers working in the area over a period of more than 30 years as part of community-based mental health programmes. There was great deal of initial resistance by the faith healers who considered the mental health professionals as competitors, but a non-confrontational approach brought home the message that indeed there are areas, particularly in cases of emotional disorders, where collaboration between the two is possible. Such collaboration has gradually been formalized in order to set up referral channels for people with mental and brain illnesses, particularly psychoses and epilepsy. Studies carried out in Pakistan have shown that there is no discernible relationship between the systems of diagnosis and treatment followed by faith healers and psychiatrists. However, the former do provide a source of care which can be harnessed constructively in order to provide culturally acceptable care to large number of people, at the same time integrating components of the local health belief model (WHO 2001).